2012
DOI: 10.1007/s00224-012-9393-4
|View full text |Cite
|
Sign up to set email alerts
|

Vertex Cover Kernelization Revisited

Abstract: An important result in the study of polynomial-time preprocessing shows that there is an algorithm which given an instance (G, k) of VERTEX COVER outputs an equivalent instance (G , k ) in polynomial time with the guarantee that G has at most 2k vertices (and thus O((k ) 2 ) edges) with k ≤ k. Using the terminology of parameterized complexity we say that k-VERTEX COVER has a kernel with 2k vertices. There is complexity-theoretic evidence that both 2k vertices and (k 2 ) edges are optimal for the kernel size. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 39 publications
(58 reference statements)
1
21
0
Order By: Relevance
“…Earlier work [8,23,25,37] has shown that several F-Minor-Free Deletion problems admit polynomial kernelizations when parameterized by the feedback vertex number. In this paper we showed that when F contains a forest and each graph in F has a connected component of at least three vertices, the F-Minor-Free Deletion problem does not admit such a polynomial kernel unless NP ⊆ coNP/poly.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier work [8,23,25,37] has shown that several F-Minor-Free Deletion problems admit polynomial kernelizations when parameterized by the feedback vertex number. In this paper we showed that when F contains a forest and each graph in F has a connected component of at least three vertices, the F-Minor-Free Deletion problem does not admit such a polynomial kernel unless NP ⊆ coNP/poly.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the decision problem, this means G has a solution of size at most with U and R as witness partite sets, if and only if G has a vertex cover of size at most − |X |. Since fvs(G ) ≤ fvs(G), we can apply the known [25] kernel for Vertex Cover parameterized by the feedback vertex number to reduce (G , − |X |) to an equivalent instance with O(fvs(G) 3 ) vertices, which is queried to the oracle. If the oracle answers positively to any query, then (G, ) has answer yes; otherwise the answer is no.…”
Section: Lemma 21mentioning
confidence: 99%
See 3 more Smart Citations